On Invariant Tori of Itô Stochastic Systems - Samoilenko, A. M.; Stanzhitskii, A. N. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
By using the Green–Samoilenko function, we establish conditions for the existence of invariant sets of Itô stochastic systems that are extensions of dynamical systems on a torus.